Membangun Kerjasama Tim di Lembaga Pendidikan pada Era Revolusi 4.0 - Lutfi Firdausi; Sulistyorini Sulistyorini (Jurnal Manajemen Pendidikan Islam (MANAPI), 2023)
In the process of interaction between a subsystem and another subsystem there is no guarantee that there will always be a conformity or match between the executing individuals. At any moment tensions may arise, both between individuals and between groups within the organization. Many factors are behind the emergence of incompatibility or tension, including different personal traits, differences in interests, poor communication, differences in values, and so on. In order for the organization to perform effectively, the interdependent individuals and groups must create a mutually supportive working relationship, towards the achievement of the organization's goals. The main challenge related to the aspect of educational institutions is to create a conducive culture and create an atmosphere that supports teamwork. The high-performance team consists of people who are truly experts in their fields, this team consists of members who have complementary skills and abilities. The foundation of a successful work team by prioritizing human relationships, effective teams are respecting each other, building discipline and building commitment so that the team can work effectively. Keywords: Leadership, Effective Team